HUBUNGAN DURASI TIDUR DAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA MAHASISWA PSKPS FK ULM - Ma’ruf, Muhamad Adi; Juhairina, Juhairina; Istiana, Istiana; Triawanti, Triawanti; Setyohadi, Dwi (Homeostasis, 2023)
Obesity is abnormal/excessive fat accumulation caused by an imbalance between energy intake and energy use over a long period of time. Factors that influence the incidence of obesity include sleep duration and physical activity. The aim of the study was to analyze the relationship between sleep duration and physical activity with the incidence of obesity in PSKPS FK ULM students. This study used an analytic observational method with a case control approach and a sampling technique using consecutive sampling, a total sample of 72 people were obtained. The data analysis used was the Chi-square test with a significance level of p value <0.05. The results showed that there was a relationship between sleep duration (p=0.002) and physical activity (p=0.004) with the incidence of obesity in PSKPS FK ULM students.